Asia Pacific business cycle: ties with Islamic stock indices - Arshad, Shahista; Duasa, Jarita; Rizvi, Syed Aun Raza (2013)
The rise of Islamic finance, in particular the Islamic equity market, has called for research in various arenas of finance and economics, in part due to evidence supporting a causal link with macroeconomic variables. One such field is the impact Islamic stock indices may have on business cycles and vice versa. This study pioneers in understanding the relationship between the volatilities of Islamic stock indices and business cycles and comparing it against their conventional counterparts. Taking daily stock returns of 12 years for Asia Pacific, our results indicated towards more volatility across Islamic stock indices during economic downturns. Inversely, Islamic stock indices appeared less volatile during the growth phase of a business cycle. The authors attributed this singularity to the small universe of stocks that make up the Asia pacific index and the heavy reliance on western and global markets for trade. This preliminary study hopes to contribute towards a dearth in literature on the understanding of the relationship between real sector business cycle and Islamic stock indices.